2022
DOI: 10.3390/microorganisms10030548
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Ohelo Berry (Vaccinium calycinum) Juice against Listeria monocytogenes and Its Potential for Milk Preservation

Abstract: Listeria monocytogenes is a foodborne pathogen and causes illnesses with a high mortality rate in susceptible populations. Several dairy-related outbreaks have been attributed to contamination by L. monocytogenes, which requires antimicrobial interventions to enhance the safety of these products. This study aimed to determine the antimicrobial activity of the ohelo berry (Vaccinium calycinum), a Hawaiian wild relative of cranberry, against L. monocytogenes in culture media and milk products. The effect of ohel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…However, the %CSH results in the presence of the highest concentration of CHY (500 µL mL −1 ) ( Figure 3 ), did not show an association with the higher aggregation observed with CLSM analysis ( Figure 2 ). As a confirmation of our results, other authors [ 32 ] have reported that L. monocytogenes ATCC 7644, in presence of cranberry extract, did not show a linear relationship between the increase of cell surface hydrophobicity and auto-aggregation. The authors argued that the association between cell hydrophobicity and aggregation in the presence of environmental stresses may be a strain-dependent trait.…”
Section: Discussionsupporting
confidence: 92%
“…However, the %CSH results in the presence of the highest concentration of CHY (500 µL mL −1 ) ( Figure 3 ), did not show an association with the higher aggregation observed with CLSM analysis ( Figure 2 ). As a confirmation of our results, other authors [ 32 ] have reported that L. monocytogenes ATCC 7644, in presence of cranberry extract, did not show a linear relationship between the increase of cell surface hydrophobicity and auto-aggregation. The authors argued that the association between cell hydrophobicity and aggregation in the presence of environmental stresses may be a strain-dependent trait.…”
Section: Discussionsupporting
confidence: 92%
“…As previously documented, Biofilm-encased bacteria likely were 10-100 times more than planktonic counterparts to be resistant to conventional antibiotics, inducing recalcitrance and recurrence of biofilm-associated uropathogenic infections (Beebout et al 2019;de Breij et al 2018). Besides, it's been reported that flagella were associated with virulence and played an essential role in colonization, adherence and distribution (Jia et al 2021;Wu et al 2022). When used E. coli Y9395 for the biofilm associated experiments because of its higher biofilm formation capability (Fig.…”
Section: Effect Of Tavaborole On the Physicochemical Properties And B...mentioning
confidence: 81%
“…Inspite of the conditions of food storage and processing, such as high salt and low temperature, infectious agent can survive and multiply because of its halotolerance and psychrotolerance ability (Jamshidi and Zeinali, 2019;Yap et al, 2021). A sustainable future requires control of antimicrobial resistance (Jeong et al, 2010;Akinduti et al, 2019;Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efficient antimicrobial approaches for preventing food contamination or the occurrence of listeriosis are urgently needed. Today, consumers desire to choose more natural, healthy, and safe food because inappropriate use of antimicrobial agents in food production might result in undesirable residues in food and the emergence of antimicrobial-resistant microorganisms (Wu et al, 2022). Excessive use of antibiotics has become a modern epidemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation